(untitled) (The Pakistan Development Review, 2010)
South Asia portrays an interesting paradox; it is the second fastest growing region in the world, yet the region has high concentration of poverty and is home to dismal social outcomes, conflicts and gender disparities. South Asia in fact is a land of two highly diverse regions; ‘Asia Shinning’ and ‘Asia Suffering’. The disparity between the two areas as lagging and leading regions is so sharp that these seem to be anchored in two different centuries. The richer region has experienced stupendous growth, due to its economic geography, globalisation and growth-promoting institutions while the limited growth potential of the poorer region has been further compounded by the weak capacity of the state to deliver social services. The question then is what should be done to address the gigantic task of poverty alleviation and take up the challenges posed by the concentration of poverty. What should be done and what the public policy can do? With a focus on this contrast as seen in Bangladesh, India, Pakistan, and Sri Lanka, the essays in this volume put into perspective the colossal task of poverty eradication and inclusive growth. The research studies included in this book not only provide fresh perspective on spatial disparities but also offer innovative, short-term as well as long-term, policy solutions to escape the poverty trap.